Multicriteria Supplier Classification for Dss: Comparative Analysis of Two Methods - Derpich-Contreras, I; Sepulveda-Salas, J (Agora University, 2015)
In this paper the analysis of two multicriteria decision making (MCDM) methods for sorting suppliers in industrial environments is presented. The MCDM methods correspond to Electre and FlowSort and both are applied to the classification of providers in an actual case of the local softdrink bottling industry in Chile. The results show that Electre as an outranking method it may well classify suppliers in a similar manner as FlowSort does. Nevertheless, due to the intrinsic underlying fuzzy multicriteria nature of the problem, FlowSort is found to be more suitable method for building a rule-based system based on preference functions for automating the process of suppliers clustering when developing strategies of relationship management in the sense of the Kraljic categories in supply chain management. © 2006-2015 by CCC Publications.